What intervention regimen is most effective prevention for Portal venous system thrombosis after splenectomy in cirrhotics patients with Portal hypertension? Systematic review and network meta-analysis. (July 2020) - Ding, Hongda; Zhang, Yingshi; Zhao, Liang; Wu, Si; Liu, Junpeng; Wang, Caibin; Pei, Tong; Su, Yang
Graphical abstract: Highlights: PVST is a life-threatening complication after splenectomy in patients with portal hypertension, interventions may prevent the incidence. While the most appropriate intervention regimen and application time for preventing the incidence of PVST is still uncertain. The application of interventions was better than no intervention use, and early application of interventions was better. Early application of low molecular weight heparin combined with low molecular dextran seems to be the most satisfactory treatment. Abstract: Portal venous system thrombosis (PVST) is a life-threatening complication after splenectomy in cirrhotics patients with portal hypertension, while the application of intervention regimen may prevent the incidence of PVST. The aim of this network meta-analysis was to determine the most appropriate intervention regimen and application time. Several electronic databases were searched up to December 2019. We estimated summary odds ratios (OR) using pairwise and network meta-analyses with random effects for the outcome of occurrence of PVST. This work was registered with PROSPERO (CRD42019161406). The analysis was based on 19 researches, which included 1853 patients. The results drawn from the data in standard meta-analysis indicated that the application of intervention was better than no intervention use, and early application of interventions was better than delayed application in preventing the occurrence of PVST. Subsequent network meta-analysis was performed to determine the most suitable intervention regimen used early post-operation. For separate mono-therapy drug, alprostadil, antithrombin III, low molecular dextran were significantly more efficacious than others. However, mono-therapy analysis was not so close to clinical application. In the follow-up network meta-analysis, low molecular dextran combined with low molecular weight heparin exhibited the largest effect on the preventing the incidence of PVST (0.12, 0.03-0.49), followed by antithrombin III (0.12, 0.04−0.41) with low molecular dextran (0.14, 0.05−0.41). We could draw the conclusion that early application of low molecular weight heparin combined with low molecular dextran seems to be the most satisfactory treatment to prevent the incidence of PVST for patients with cirrhotic portal hypertension after splenectomy.